2022
DOI: 10.1002/cbdv.202200069
|View full text |Cite
|
Sign up to set email alerts
|

Hieracium waldsteinii (Asteraceae) and Onosma stellulata (Boraginaceae) as a Source of Antioxidant and Antimicrobial Agents

Abstract: The current study aimed to phytochemically characterize (including a detailed phenolic profile) two endemic Balkan's species (Hieracium waldsteinii and Onosma stellulata) and determine their possible application as a source of natural antioxidant and antimicrobial agents. The main phenolic compound in both species (in all examined parts) was chlorogenic acid. Eriodictyol, genistein and naringenin were quantified only in H. waldsteinii while isorhamnetin‐3‐O‐rutinoside and sinapic acid were characteristic for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…As for other previously investigated Hieracium species, it can be observed that the activity of dry 80 % MeOH extracts of leaves, stems and flowers of H. waldsteinii against bacteria S. aureus , B. cereus , L. monocytogenes , S. Typhimurium , E. coli , E. cloacae and P. aeruginosa , and fungi A. fumigatus , A. versicolor , A. ochraceus , T. viride , P. funiculosum and P. verrucosum var. cyclopium , determined in the same microdilution test, was in many cases comparable to the activity of Hieracium extracts investigated in this work; regarding activity of H. waldsteinii extracts against Micrococcus luteus , it was better than the activity of our Hieracium extracts against other tested species of this genus, M. flavus [11] . As for hexane extracts of H. umbellatum roots, leaves and stems, their antimicrobial activity against E. coli was assessed by modified microdilution method, based on measurement of optical density; roots and stems extracts showed weak activity and leaves extract was not active [9]…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…As for other previously investigated Hieracium species, it can be observed that the activity of dry 80 % MeOH extracts of leaves, stems and flowers of H. waldsteinii against bacteria S. aureus , B. cereus , L. monocytogenes , S. Typhimurium , E. coli , E. cloacae and P. aeruginosa , and fungi A. fumigatus , A. versicolor , A. ochraceus , T. viride , P. funiculosum and P. verrucosum var. cyclopium , determined in the same microdilution test, was in many cases comparable to the activity of Hieracium extracts investigated in this work; regarding activity of H. waldsteinii extracts against Micrococcus luteus , it was better than the activity of our Hieracium extracts against other tested species of this genus, M. flavus [11] . As for hexane extracts of H. umbellatum roots, leaves and stems, their antimicrobial activity against E. coli was assessed by modified microdilution method, based on measurement of optical density; roots and stems extracts showed weak activity and leaves extract was not active [9]…”
Section: Resultssupporting
confidence: 84%
“…Previously investigated polar extracts of H. waldsteinii leaves, stems and flowers (on HT29 – human colon adenocarcinoma) and H. umbellatum flowering aerial parts (on HeLa, MCF7 – human breast adenocarcinoma and A431 – human skin epidermoid carcinoma) showed weak activity or were not active at maximal tested concentrations of 10 μg/mL ( H. umbellatum ) and 500 μg/mL ( H. waldsteinii ) [10,11] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations